ChemInform Abstract: Direct α‐Alkylation of Ketones with Alcohols in Water. Issue 31 (5th August 2014) - Xu, Guoqiang; Li, Qiong; Feng, Jiange; Liu, Qiang; Zhang, Zuojun; Wang, Xicheng; Zhang, Xiaoyun; Mu, Xindong
Abstract A new and green C—C bond formation in water is developed.